2022
DOI: 10.1097/cm9.0000000000001944
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal aortic balloon occlusion in the management of placenta percreta

Abstract: Background:Massive bleeding is the main concern for the management of placenta percreta (PP). Intra-abdominal aortic balloon occlusion (IABO) is one method for pelvic devascularization, but the efficacy of IABO is uncertain. This study aims to investigate the outcomes of IABO in PP patients.Methods:We retrospectively reviewed the clinical data of PP cases from six tertiary centers in China between January 2011 and December 2015. PP cases with/without the use of IABO were analyzed. Propensity score matching ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The modalities of PBO varied in many hospitals and published results are conflicting and do not allow the extrapolation of robust evidence on the actual role of PBO in improving the outcome of PAS [24]. For instance, a previous meta-analysis and some retrospective research reported that balloon occlusion of IIA had benefits in reducing blood loss, blood transfusion, and even the rate of hysterectomy in women with placenta accreta [17,[25][26][27]. Nevertheless, one recent study showed that PBO was associated with reduced blood loss only for patients who underwent AA balloon occlusion [28].…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…The modalities of PBO varied in many hospitals and published results are conflicting and do not allow the extrapolation of robust evidence on the actual role of PBO in improving the outcome of PAS [24]. For instance, a previous meta-analysis and some retrospective research reported that balloon occlusion of IIA had benefits in reducing blood loss, blood transfusion, and even the rate of hysterectomy in women with placenta accreta [17,[25][26][27]. Nevertheless, one recent study showed that PBO was associated with reduced blood loss only for patients who underwent AA balloon occlusion [28].…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…Resuscitative endovascular balloon occlusion of the aorta has been used for life-threatening postpartum haemorrhage, with promising results in observational studies [ 56 ]. An abdominal aortic balloon has also been placed prior to CS in cases of placenta accreta spectrum [ 57 ]. Observational studies suggest improved outcomes with balloon occlusion of the abdominal aorta, the common ileac arteries or the internal ileac arteries [ 58 , 59 ].…”
Section: Endovascular Balloon Occlusion Of the Aorta Common Ileac Art...mentioning
confidence: 99%
“…В многочисленных публикациях сообщалось, что ВБОБА может быть безопасным и эффективным методом при оперативном родоразрешении пациенток с приращением плаценты, способствует снижению объёма кровопотери во время кесарева сечения и снижает риски, связанные с гистерэктомией [46][47][48][49][50][51][52][53][54][55]. В то же время клиническая эффективность профилактической БОПА была описана различными авторами с различными результатами (табл.…”
Section: временная баллонная окклюзия брюшного отдела аорты (вбоба)unclassified